THE FORMATION OF SOCIAL CHARACTER TO COUNTER THE PRACTICE OF USURY IN PESANTREN ENVIRONMENTS - Nurmawan, Nurmawan; Sulastri, Rini (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: The widespread practice of usury with high interest rates targets various segments of society, including those in pesantren communities. To address the issues faced by individuals in the vicinity of pesantren, the formation of social solidarity for collective welfare is essential. Purpose: This study aims to examine the process of social character formation among members of the Pesantren Persis Ciganitri community, specifically through activities in the *Halaqoh Mingguan* (Halmi) program. Method: The research employs a qualitative descriptive method. Data were collected through observation, interviews, documentation study, and Focus Group Discussions (FGD). Result: The results of this study reveal that the process of social character formation occurs through learning activities conducted by teachers (ustad, ustadzah), as well as supervisors or officials from the Micro Waqf Bank Berkah Umat Ciganitri. Learning is carried out through lectures aimed at instilling social and religious values embedded in an oath. This oath, recited at each meeting, serves as a commitment from the members to improve their economy through halal (permissible) business practices and to enhance their children's education. Conclusion: The outcomes of this social character formation within the Halmi program include cooperation, social solidarity, respect for differences, and cultural assimilation—values that reflect the social character shaped through these Halmi activities.